Analisis Financial Distress Altman Z-Score: Studi Perusahaan Food And Beverage Tahun 2024 - Kresnawati, Ila; Kusumawardani, Anisa (Multidisciplinary Journal of Education , Economic and Culture, 2026)
This study aims to analyze the financial distress condition of food and beverage companies listed on Indonesia Stock Exchange during the 2024 period using the Altman Z-Score model. Financial distress is an important indicator that reflects a company’s financial health and potential bankruptcy risk. The study employed a quantitative descriptive approach using secondary data obtained from annual financial reports of food and beverage companies. The analysis was conducted by calculating the Altman Z-Score through financial ratio indicators consisting of working capital to total assets, retained earnings to total assets, earnings before interest and taxes to total assets, and market value equity to book value of liabilities. The findings indicate that the majority of companies are classified in the safe zone, reflecting relatively stable financial conditions and a low risk of bankruptcy. However, several companies were identified in the grey zone and distress zone, indicating potential financial difficulties and the need for improvement in financial performance and operational efficiency. The highest Z-score was achieved by CMRY with a score of 13.5885, while the lowest score was recorded by BOBA with a value of 1.10987.